Lost and found media sales. - Cherry, S.M (IEEE spectrum)
Does file-sharing of copyrighted material harm sales today? The movie, music and book trade associations say it does, but for each form of entertainment, a growing body of evidence suggests otherwise-and not all of the evidence is anecdotal. In a study of about 3,000 individuals, research firm Jupiter Media Metrix Inc. found that "experienced file-sharers are more likely to actually increase the amount of money they spend on CDs." 34% said they spent more than before on music, twice as many as said they spent less (15%). One ongoing real-life experiment is the Baen Free Library. The novels in this Web-based collection are made available at no charge and in their entirety by science fiction publisher Baen Books. It seems that a free online copy can boost sales of movies, records and books